Presence, quantitation and characterization of JC virus in the urine of Italian immunocompetent subjects - Rossi, Andrea; Delbue, Serena; Mazziotti, Romina; Valli, Marilena; Borghi, Elisa; Mancuso, Roberta; Calvo, Maria G.; Ferrante, Pasquale (Journal of medical virology, 2007)
Human polyomavirus JC (JCV) infects the worldwide population, remains latent in the kidney, and is excreted in the urine. A longitudinal study was performed in order to evaluate JCV excretion, to characterize molecularly the virus and to determine if its presence in urine is a consequence of viral reactivation or merely of epithelial squamous cell shedding. The presence of cellular sediment and the JCV genome were examined in 333 urine samples collected periodically for 3 months from 17 healthy subjects; molecular characterization, and quantitation of the virus were also undertaken. JCV DNA was detected in 40.2% of the samples, with a significant difference (P < 0.001) observed between males and females. JCV shedding was independent of the presence of cellular sediment in every individual. JCV genotype 1 was the genome detected most frequently, while all of the amplified strains showed archetypal organization of the transcriptional control region (TCR). No clinical symptoms have been associated with JCV excretion and no microbial load was detected in the urine samples. The lack of correlation between JCV DNA detection and the presence of squamous cells in urine sediment indicates that viruria is regulated by the life cycle of JCV. Thus, the virus is eliminated as consequence of its reactivation. J. Med. Virol. 79:408–412, 2007. © 2007 Wiley‐Liss, Inc.